The Influence of Knowledge and Financial Attitudes on The Financial Management Behavior of Faculty of Economics and Business Students at Tadulako University Moderate by Digital Literacy - Ahmad Syahib Hidayat; Muhammad Yunus Kasim; Vitayanti Fattah; Nur Riski Islianty (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of financial knowledge and financial attitudes on the financial management behavior of students at the Faculty of Economics and Business, Tadulako University, with digital literacy as a moderating variable. Using a quantitative survey approach, data were collected through purposive sampling from undergraduate students in management, accounting, and development economics who earn income, manage personal finances, and use digital media for financial activities. The findings show that financial knowledge and financial attitudes positively and significantly influence financial management behavior. However, digital literacy does not moderate these relationships. Keywords: Finance; Knowledge; Attitude; Behavior; Students